The Mystery of the Missing Antimatter. - Quinn, Helen R. (Science essentials (National Academy of Sciences (U.S.)), 2010)
In the first fractions of a second after the Big Bang lingers a question at the heart of our very existence: why does the universe contain matter but almost no antimatter? The laws of physics tell us that equal amounts of matter and antimatter were produced in the early universe--but then, something odd happened. Matter won out over antimatter; had it not, the universe today would be dark and barren. But how and when did this occur? Helen Quinn and Yossi Nir guide readers into the very heart of this mystery--and along the way offer an exhilarating grand tour of cutting-edge physics. They expla.